Two Functionally Deviating Type 6 Secretion Systems Occur in the Nitrogen-Fixing Endophyte Azoarcus olearius BH72 - Jiang, Xun; Beust, Andreas; Sappa, Praveen K.; Völker, Uwe; Dinse, Theresa; Herglotz, Julia; Reinhold-Hurek, Barbara (Frontiers in Microbiology, 2019)
Type VI protein secretion systems (T6SS) have been identified in many plant-associated bacteria. However, despite the fact that effector proteins may modulate host responses or interbacterial competition, only a few have been functionally dissected in detail. We dissected the Type VI protein secretion system in Azoarcus olearius strain BH72, a nitrogen-fixing model endophyte of grasses. The genome harbors two gene clusters encoding putative T6SSs, tss-1 and tss-2, of which only T6SS-2 shared genetic organization and functional homology with the H1-T6SS of Pseudomonas aeruginosa. While tss-2 genes were constitutively expressed, tss-1 genes were strongly up-regulated under conditions of nitrogen fixation. A comparative analysis of the wild type and mutants lacking either functional tss-1 or tss-2 allowed to differentiate the functions of both secretion systems. Abundance of Hcp in the culture supernatant as an indication for T6SS activity revealed that only T6SS-2 was active, either under aerobic or nitrogen-fixing conditions. Our data show that T6SS-2 but not T6SS-1 is post-translationally regulated by phosphorylation mediated by TagE/TagG (PpkA/PppA), and by the phosphorylation-independent inhibitory protein TagF, similar to published work in Pseudomonas. Therefore, T6SS-1 appears to be post-translationally regulated by yet unknown mechanisms. Thus, both T6SS systems appear to perform different functions in Azoarcus, one of them specifically adapted to the nitrogen-fixing lifestyle